Seoul the making of a metropolis - Kim, Joochul (World cities series, 1997)
Examines the emergence of Seoul from a small walled-in city to a modern metropolis, providing a case study for urban planners and geographers throughout the world. The text provides a description of factors affecting the growth of Seoul. Seoul continues to face huge challenges. Its impressive growth took place during only 30 - 35 years, the population exploded, physical size expanded continuously, economic development intensified and industries diversified. Seoul with a current population of more than 11 million has become a dominant capital city. With a force of strong political decentralization, Seoul confronts an even greater challenge of learning to work with citizens and creating a liveable city.